Governmentality of the Arctic as an international region. (March 2018) - Albert, Mathias; Vasilache, Andreas
Linked to the image of a wild and still-to-be-explored territory, as well as to images of the region as one of new economic opportunities, discourses on the Arctic also tie in with issues of climate change, cooperation and conflict, Arctic governance, international law and the situation and rights of indigenous people, as well as Great Power politics. Taken together, these aspects characterize a region whose formation is different from regionalization processes in other parts of the world. As the regional peculiarity of the Arctic is reflected by a variety and plurality of representations, discourses, perceptions and imaginaries, it can usefully be analyzed as a region of unfolding governmentality. The present article argues that the prospects for the Arctic are strongly intertwined with perceptions and depictions of it as an international region subject to emerging practices of governmentality. By drawing on both Foucault's texts and governmentality studies in international relations (IR), we discuss how the Arctic is affected by governmental security rationalities, by specific logics of political economy and order-building, as well as becoming a subject for biopolitical rationalizations and imaginaries. The discourses and practices of governmentality that permeate the Arctic contribute to its spatial, figurative and political reframing and are aimed at making it a governable region that can be addressed by, and accessible for, ordering rationalities and measures.